Douglas Walton’s Contributions in Education: A Synthesis of Theoretical and Empirical Research - Rapanta, Chrysi (Informal Logic, 2022)
Douglas Walton, perhaps the most prolific author in Argumentation theory, has been of a great influence in the fields of Informal logic, Artificial intelligence, and Law. His contributions in the field of educational research, in particular in the field of argumentation and education, are less known. This review paper aims at shedding light on those aspects of Walton’s theory that have received educational researchers’ attention thus far, as well identifying existing lacks of consideration and open paths for future research.